A Study of Statistical Properties & Model Validation for Exponential Extension Model - Srivastava, Ashwini Kumar (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
In this paper, we study the statistical properties of Exponential Extension Model and then we also check the validity of proposed model for different real data sets through different techniques. We are using two main techniques which are easy to understand and implement, and are based on intuitive and graphical techniques such as Q-Q-plot test, Kolmogorov–Smirnov (K-S) test which plot the graph of empirical distribution function and fitted distribution function. These plots are used to investigate whether an assumed model adequately fits a set of data and we present power comparison between p-values of these data sets obtaining by K-S test for model validation to obtain feasible real data sets which are most suitable for parameter estimation of exponential extension model.